Efforts to Increase Fatherless Students' Learning Motivation Through A Learning Approach Based on Psychosocial Support in Primary Schools - Hanipah, Nida; Yuliyanto, Aan; Amanaturrakhmah, Isna; Agustin, Della Rahayu; Sa’diyah, Salsa Reza; Asyifa, (International Conference on Elementary Education, 2025)
Fatherless students are those who grow up without the physical or emotional presence of a father, often encountering challenges in emotional and social support, which can significantly affect their learning motivation. This study employs a systematic literature review method by analyzing 20 peer-reviewed journal articles published between 2015 and 2024 that explore psychosocial support in primary education and its impact on student motivation. The selection of sources was based on relevance, methodological rigor, and focus on psychosocial interventions. The findings reveal that structured psychosocial support from teachers and the school environment plays a crucial role in enhancing self-confidence, classroom participation, and social engagement among fatherless students. These results were synthesized from qualitative analyses of student self-reports, teacher observations, and standardized motivation assessment tools used in the reviewed studies. The study concludes that psychosocial support-based learning approaches can effectively help fatherless students overcome emotional and social barriers, thereby significantly improving their learning motivation.